2020
DOI: 10.1371/journal.pntd.0008249
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara species environmental contamination of public spaces in New York City

Abstract: Human toxocariasis has been identified as an under-diagnosed parasitic zoonosis and health disparity of significant public health importance in the United States due to its high seropositivity among socioeconomically disadvantaged groups, and possible links to cognitive and developmental delays. Through microscopy and quantitative PCR, we detected that Toxocara eggs are widespread in New York City public spaces, with evidence of significant levels of contamination in all five boroughs. The Bronx had the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 40 publications
2
43
1
Order By: Relevance
“…Such high seroprevalence warrants a clinical investigation as covert toxocariasis would be a serious concern among the studied children [ 3 ]. Further, evidence indicates strong links between seropositivity and cognitive and developmental delays [ 1 , 4 , 5 , 27 , 28 ]. To reinforce the plausible link between seropositivity and health effects, we found that after controlling for STH infections, the presence of anti- Toxocara antibodies was associated with high levels of eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such high seroprevalence warrants a clinical investigation as covert toxocariasis would be a serious concern among the studied children [ 3 ]. Further, evidence indicates strong links between seropositivity and cognitive and developmental delays [ 1 , 4 , 5 , 27 , 28 ]. To reinforce the plausible link between seropositivity and health effects, we found that after controlling for STH infections, the presence of anti- Toxocara antibodies was associated with high levels of eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that this infection may partially account for cognitive deficits and other neurological complications seen among socioeconomically disadvantaged children [ 1 , 4 ]. There is a strong body of research from Europe and South America and a recent interest resurgence in the United States [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] 2016: 14-month-old canine with hookworm invasion of the brainstem, TX ( Ancylostoma spp. ) [ 38 ] Trichuris trichiura (whipworm) unavailable Highest: 55.2% in 366 Native born School children ages 6–12, KY Lowest:: 0.5% in 3729 Caucasian school children ages 5–15, GA unavailable Strongyloides stercoralis 68,000 – 100,000[ 26 ] Highest: 3.8% in 366 Native born School children ages 6–12, KY Lowest: 0% in 439 School children ages 10–14, KY 2020: 68-year -old man with COVID-19 infection immigrating 20 years prior from Ecuador, CT 2020: 16.5% positive serology in 97 individuals from a community with failing sanitation/poverty, central TX (75% with no travel history) [ 13 ••] 2017: 61-year old US-born man with HIV coinfection, no significant travel history, CT [ 11 ] 2017: 7.3% stool samples from 55 individuals in area of failing sanitation and poverty, Lowndes County, AL [ 24 ] 2013: 1.9% in 378 positive serology from persons presenting to Remote Area Medical Clinics, KY (only 1 positive participant had significant travel history) [ 28 ] Toxocara canis , T. cati 1.3–2.8 million [ 26 ] unavailable 2019: 3-year-old girl with OLM, previously healthy presenting with blurry vision and headache, AK [ 33 ] 2017: 5.2% positive serology from 11 individuals testing positive for any GI parasites in area of failing sanitation and poverty, Lowndes County, AL [ 24 ] 2015–2016: 66.7% contamination with eggs & larvae in 10/15 soil samples from the Bronx, 38.9% in 7/18 soil samples from Staten Island, 33.3% in 6/18 soil samples from Queens, 30.8% 4/13 soil samples from Brooklyn, 29.6% in 8/27 soil samples from Manhattan, NY [ 39 ] 2014: 4.6% egg positive fecal samples from 523,934 cats and 1.8% egg positive fecal samples from 2,750,718 dogs, national [ 40 ] 2014: 75-year-old female with pulmonary toxocariasis (only travel history 15 years prior to Caribbean), NJ [ 41 ] 2011–2014: 5.1% overall seroprevalence from 13,509 individuals from NHANES 2011–2014, national [ 42 ] 2009–2010: 68 case reports of OLM in individuals aged 1–60, national [ 43 ] …”
Section: What Is Known About Sth In the Usa?: Past And Presentmentioning
confidence: 99%
“…2015–2016: 66.7% contamination with eggs & larvae in 10/15 soil samples from the Bronx, 38.9% in 7/18 soil samples from Staten Island, 33.3% in 6/18 soil samples from Queens, 30.8% 4/13 soil samples from Brooklyn, 29.6% in 8/27 soil samples from Manhattan, NY [ 39 ]…”
Section: What Is Known About Sth In the Usa?: Past And Presentmentioning
confidence: 99%
“…There is increasing evidence that tropical diseases are also causative for propagating poverty in those infected [ 24 ]. In the USA, an urban study in New York City reported a direct correlation with more Toxocara parasite in city parks from poor neighborhoods compared with rich boroughs [ 25 ]. Another study in a clinic that serves low-income patients located in Washington D.C. was found to have endemic levels of a potentially dangerous parasite called Strongyloides stercoralis in this low-income population [ 26 ].…”
Section: Covid-19 and Its Relationship With Tropical Diseasesmentioning
confidence: 99%